2005
DOI: 10.1097/01.prs.0000156988.78391.d6
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Recovery in the Sensate Free Transverse Rectus Abdominis Myocutaneous Flap

Abstract: The authors' findings confirm that reinnervation of microsurgically reconstructed breasts achieves sensory recovery that is superior to that in breasts reconstructed without reinnervation. If sensation is important and the anatomical factors are favorable, reinnervation may represent a worthwhile refinement in attempts to achieve normality for patients undergoing breast reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 23 publications
(25 reference statements)
3
46
0
1
Order By: Relevance
“…Since the first description of reinnervation of the abdominal wall flap by coapting the sensory innervation to the flap with a branch of the fourth intercostal nerve (Slezak et al, 1992), the clinical efficacy of the technique has been confirmed, but the anatomical basis has been disputed, particularly the segmental origins of the donor-site nerves (Allen and Treece, 1994;Liew et al, 1996;Blondeel et al, 1999;Yap et al, 2005;Temple et al, 2006).…”
Section: Clinical Applicationsmentioning
confidence: 96%
“…Since the first description of reinnervation of the abdominal wall flap by coapting the sensory innervation to the flap with a branch of the fourth intercostal nerve (Slezak et al, 1992), the clinical efficacy of the technique has been confirmed, but the anatomical basis has been disputed, particularly the segmental origins of the donor-site nerves (Allen and Treece, 1994;Liew et al, 1996;Blondeel et al, 1999;Yap et al, 2005;Temple et al, 2006).…”
Section: Clinical Applicationsmentioning
confidence: 96%
“…80 Sensation of free TRAM and DIEP flaps can be improved by coaptation of recipient cutaneous intercostal nerve branches to a single thoracoabdominal nerve in the flap. 81,82 The DIEP flap is usually raised on only one or two perforators, potentially making this flap more prone to fat necrosis than free TRAM flaps of comparable size. 70 Extra caution should be taken when harvesting large flaps (i.e., Ͼ400 g), especially in diabetic or smoking patients.…”
Section: Free Diep Flapmentioning
confidence: 99%
“…Reinnervation pilot studies have demonstrated recovery of sensation in immediate breast reconstruction with the latissimus flap [61], TRAM flaps [59], and perforator flaps [60]. The reinnervation techniques show different recovery patterns than those seen in nonreinnervated flaps, specifically with respect to temperature and fine touch, which may offer an element of protection to patients [59]. Larger prospective studies still need to be done to justify these procedures and further define the sensory innervation.…”
Section: Emerging Therapiesmentioning
confidence: 95%
“…• Mastectomy sacrifices sensory nerves to the breast, causing loss of sensation of the reconstructed breast mound. Despite reports of spontaneous return of sensation over time, several authors have advocated nerve repair at the time of breast reconstruction, to increase the quality and quantity of flap sensation [59,60]. Reinnervation pilot studies have demonstrated recovery of sensation in immediate breast reconstruction with the latissimus flap [61], TRAM flaps [59], and perforator flaps [60].…”
Section: Emerging Therapiesmentioning
confidence: 98%
See 1 more Smart Citation